A Population of Radio-Resistant Macrophages in the Deep Myenteric Plexus Contributes to Postoperative Ileus Via Toll-Like Receptor 3 Signaling - Enderes, Jana; Mallesh, Shilpashree; Schneider, Reiner; Hupa, Kristof J.; Lysson, Mariola; Schneiker, Bianca; Händler, Kristian; Schlotmann, Balthasar; Günther, Patrick; Schultze, Joachim L.; Kalff, Jörg C.; Wehner, Sven (Frontiers in Immunology, 2021)
Postoperative ileus (POI) is triggered by an innate immune response in the muscularis externa (ME) and is accompanied by bacterial translocation. Bacteria can trigger an innate immune response via toll-like receptor (TLR) activation, but the latter’s contribution to POI has been disproved for several TLRs, including TLR2 and -4. Herein we investigated the role of double-stranded RNA detection via TLR3 and TIR-domain-containing adapter-inducing interferon-β (TRIF) signaling pathway in POI. POI was induced by small bowel intestinal manipulation in wt, TRIF-/-, TLR3-/-, type I interferon receptor-/- and interferon-β reporter mice, all on C57BL/6 background, and POI severity was quantified by gene expression analysis, gastrointestinal transit and leukocyte extravasation into the ME. TRIF/TLR3 deficiency reduced postoperative ME inflammation and prevented POI. With bone marrow transplantation, RNA-sequencing, flow cytometry and immunohistochemistry we revealed a distinct TLR3-expressing radio-resistant MHCIIhiCX3CR1- IBA-1+ resident macrophage population within the deep myenteric plexus. TLR3 deficiency in these cells, but not in MHCIIhiCX3CR1+ macrophages, reduced cytokine expression in POI. While this might not be an exclusive macrophage-privileged pathway, the TLR3/TRIF axis contributes to proinflammatory cytokine production in MHCIIhiCX3CR1- IBA-1+ macrophages during POI. Deficiency in TLR3/TRIF protects mice from POI. These data suggest that TLR3 antagonism may prevent POI in humans.